2018
DOI: 10.1016/j.ymthe.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Human CD19-Targeted Mouse T Cells Induce B Cell Aplasia and Toxicity in Human CD19 Transgenic Mice

Abstract: The clinical success of chimeric antigen receptor (CAR) T cell therapy for CD19 B cell malignancies can be limited by acute toxicities and immunoglobulin replacement needs due to B cell aplasia from persistent CAR T cells. Life-threatening complications include cytokine release syndrome and neurologic adverse events, the exact etiologies of which are unclear. To elucidate the underlying toxicity mechanisms and test potentially safer CAR T cells, we developed a mouse model in which human CD19 (hCD19)-specific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 67 publications
(135 reference statements)
2
38
0
Order By: Relevance
“…To address this, my research group, in collaboration with Michael Jensen's laboratory, has recently developed the first nonhuman primate (NHP) model of CRS and neurologic toxicity, using CD20 CAR-T cells in rhesus macaques 171 and Bruce Blazar's group has recently developed a mouse model of CAR-T toxicity, in which human CD19-specific mouse CAR-T cells were adoptively transferred into mice whose normal B cells express a hCD19 transgene at hemizygous levels. 172 Using the NHP model, we demonstrated CAR-T-cell expansion and B-cell aplasia, as well as CRS and neurotoxicity that closely mirrors what has been observed clinically. 171 Thus, this model induces elevations in the serum of multiple cytokines, and has documented disproportionately high concentrations of several cytokines in the CSF.…”
Section: Preinfusion Chemotherapysupporting
confidence: 71%
“…To address this, my research group, in collaboration with Michael Jensen's laboratory, has recently developed the first nonhuman primate (NHP) model of CRS and neurologic toxicity, using CD20 CAR-T cells in rhesus macaques 171 and Bruce Blazar's group has recently developed a mouse model of CAR-T toxicity, in which human CD19-specific mouse CAR-T cells were adoptively transferred into mice whose normal B cells express a hCD19 transgene at hemizygous levels. 172 Using the NHP model, we demonstrated CAR-T-cell expansion and B-cell aplasia, as well as CRS and neurotoxicity that closely mirrors what has been observed clinically. 171 Thus, this model induces elevations in the serum of multiple cytokines, and has documented disproportionately high concentrations of several cytokines in the CSF.…”
Section: Preinfusion Chemotherapysupporting
confidence: 71%
“…We acknowledge that the xenograft model used here underestimates the role of myeloid cells in the context of CRS. 22,23,27 Nonetheless, clinical data from numerous studies indicate that CRS severity is tightly linked to CAR-T cell expansion; thus, dasatinib-mediated inhibition of CAR-T cell expansion would be expected to provide a potent therapeutic for CRS. Established models of CRS 22,23,27 could be informative for comparing the relative effectiveness of dasatinib with that of tocilizumab and/or corticosteroids.…”
Section: Resultsmentioning
confidence: 99%
“…To date, animal models have demonstrated that the severity of immune toxicities is associated with IL6, IL1, and nitric oxide produced by macrophages (8)(9)(10)(11). However, there remains a need to validate these observations and use accessible laboratory tests to diagnose, monitor, and/or prognosticate toxicities.…”
Section: Introductionmentioning
confidence: 99%